Clinico-epidemiological study of stasis eczema - Shankar, S. Vijay; Shariff, V. N. S. Ahamed; Nirmala, S. (International Journal of Research in Medical Sciences, 2017)
Background: This study was done to determine the epidemiological aspects of stasis eczema and the association of various risk factors of the disease in the local population. Methods: This cross-sectional study was done at a tertiary hospital in southern India over a period of 1 year. Epidemiological and clinical data of stasis dermatitis patients above 20 years of age were recorded. Data was tabulated and analyzed using Microsoft excel software. Results: Of the study population of 120 prevalence is found to be highest in the age group of 50 to 60 years (42.5%) and males are more commonly affected. Occupation involving prolonged standing or sitting and lack of exercise activity is found to be a significant risk factor. The commonest skin finding in present study is eczema (80%). The most common complication was ulcer which was seen in 12.5% of our patients. Reticular veins are the most common dilated veins seen in our patients. About 70% of patients in present study fall under C4a stage of CEAP classification. About one half of symptomatic patients in present study (53.3%) had no radiological evidence of incompetent veins. Among patients with valvular incompetence, perforator veins were most commonly found to be incompetent (62.5%) followed by involvement of the saphenous venous system (23.2%). Conclusions: The study confirms the importance of environmental factors in the development of stasis eczema. There is a ten-fold higher prevalence of the disease in men in our population compared to previous studies which invariably reports a female preponderance.